Pengaruh Organizational Citizenship Behavior (OCB) terhadap Produktivitas Kerja di Kalangan Pegawai Sekretariat Daerah Kota Bukittinggi - Fayed, Fahren Al; Syamsir, Syamsir (Lembaga Yasin AlSys, 2025)
This study is motivated by the importance of enhancing employee productivity in governmental institutions through extra-role behavior, or Organizational Citizenship Behavior (OCB), which has yet to be fully optimized. The aim of this research is to examine the influence of OCB on the work productivity of employees at the Regional Secretariat of Bukittinggi City. A quantitative approach with an associative research design was employed. The population consisted of 101 civil servants (ASN) and government employees under contract (P3K), with a sample of 80 respondents determined using Slovin’s formula and selected through simple random sampling. Data were collected using a closed-ended questionnaire based on a four-point Likert scale and analyzed using SPSS version 25. The instrument’s validity and reliability were tested using item-total correlation and Cronbach’s Alpha. Analytical techniques included descriptive analysis, classical assumption tests (normality and linearity), and simple linear regression. The results showed that employee OCB levels were categorized as high, and work productivity was considered good. A positive and significant influence was found between OCB and work productivity, indicating that the higher the OCB, the greater the employee productivity. These findings underscore the vital role of OCB in improving public sector employee performance. This study contributes to the development of organizational behavior research and recommends further exploration of additional variables such as motivation or organizational culture to enrich future analyses.